The Effectiveness of Problem-Based Learning Chemistry Modules and Their Impact on Students’ Critical Thinking Abilities - Rika Wulandari; Isana Supiah YL (Jurnal Penelitian Pendidikan IPA, 2023)
The research aims to assess the effectiveness of using problem-based learning-oriented chemical bonding modules in improving students' critical thinking skills. This study falls under the category of Research and Development with a four-D product development model. The research design employs a quasi-experimental approach with a post-test-only control group design using experimental and control classes for comparison. Effectiveness assessment is carried out using interview guidelines, observation sheets, and tests to determine students' critical thinking abilities. The effectiveness analysis technique involves independent sample t-tests and Cohern's effect size. The results of the independent sample t-test indicate a difference in students' critical thinking abilities before and after using problem-based learning-oriented chemical bonding modules. The effect size values suggest a moderate level of effective contribution, ranging from 0.20 to 0.80. Consequently, the research findings conclude that problem-based learning-oriented chemical bonding modules are effective in enhancing students' critical thinking skills